Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1038/sj.bjc.6601670
|View full text |Cite
|
Sign up to set email alerts
|

TNF autovaccination induces self anti-TNF antibodies and inhibits metastasis in a murine melanoma model

Abstract: TNF is a proinflammatory cytokine involved in the pathogenesis of chronic inflammatory diseases, but also in metastasis in certain types of cancer. In terms of therapy, TNF is targeted by anti-TNF neutralising monoclonal antibodies or soluble TNF receptors. Recently, a novel strategy based on the generation of self anti-TNF antibodies (TNF autovaccination) has been developed. We have previously shown that TNF autovaccination successfully generates high anti-TNF antibody titres, blocks TNF and ameliorates colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…Vaccination toward TNF triggers self anti-TNF antibodies and inhibits lung invasion of intravenously injected B16 melanoma cells (14). Similar data have been obtained by injecting anti-TNF-neutralizing antibodies (14) or soluble TNF-R1 (15), indicating that TNF blockade may represent a useful strategy to prevent melanoma metastasis. A recent study showed that TNF deficiency can delay tumor growth in a spontaneous mouse model of BRAF V600E melanoma (16).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Vaccination toward TNF triggers self anti-TNF antibodies and inhibits lung invasion of intravenously injected B16 melanoma cells (14). Similar data have been obtained by injecting anti-TNF-neutralizing antibodies (14) or soluble TNF-R1 (15), indicating that TNF blockade may represent a useful strategy to prevent melanoma metastasis. A recent study showed that TNF deficiency can delay tumor growth in a spontaneous mouse model of BRAF V600E melanoma (16).…”
Section: Introductionsupporting
confidence: 66%
“…Moreover, lung invasion of intravenously injected B16 melanoma cells is decreased in TNF À/À and TNF-R2 À/À mice, indicating that TNF likely enhances melanoma dissemination in a TNF-R2-dependent manner (13). Vaccination toward TNF triggers self anti-TNF antibodies and inhibits lung invasion of intravenously injected B16 melanoma cells (14). Similar data have been obtained by injecting anti-TNF-neutralizing antibodies (14) or soluble TNF-R1 (15), indicating that TNF blockade may represent a useful strategy to prevent melanoma metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma, preclinical models have shown that TNF can induce cell invasion 2 and angiotropism, 3 thus increasing the likelihood of intravasation and hematogenous dissemination; dedifferentiation, and thereby impaired sensitivity to melanocyte-differentiation antigen (MDA)-directed CD8 C immune responses; 4 trigger effector CD8 C T cell death impairing accumulation of CD8 C T cells in the tumor microenvironment. 5 Importantly, TNF inhibition prevents lung metastatization in animal models 6 and, in contrast to earlier reports, it is now demonstrated that chronic treatment with TNF inhibitors does not increase the risk of developing melanoma in human subjects. 7 Our recent studies add additional insights to the puzzling roles of TNF in cancer, pointing out tumor-specific CD4 C T cells as one major source of TNF in the tumor microenvironment of metastatic melanoma in humans driven by tumor MHC class II expression.…”
mentioning
confidence: 57%
“…More recently, TNF autovaccination has been successfully tested in the murine B16F10 melanoma model to inhibit the metastatization process in vivo [94]. Other investigators used TNF-R1 À/À mice to show that endogenous TNF is crucial for promoting liver metastasis after intrasplenic administration of a colonic adenocarcinoma cell line [95]: more than 90% of wild-type mice develop liver metastases compared with less than 50% of TNF-R1 À/À mice; the difference in metastatic behavior is associated with increased VCAM-1 expression in the livers of wild-type animals, which is instead significantly attenuated in TNF-R1 À/À mice.…”
Section: Tnf and Cancer Progressionmentioning
confidence: 99%